2013
DOI: 10.1115/1.4025876
|View full text |Cite
|
Sign up to set email alerts
|

Modal Analysis of General Plate Structures

Abstract: A general analytical method, referred to as the Fourier spectral element method, is presented for the dynamic analysis of plate structures consisting of any number of arbitrarily oriented rectangular plates. The compatibility conditions between any two adjacent plates are generally described in terms of three-dimensional elastic couplers with both translational and rotational stiffnesses. More importantly, all plates involved can be arbitrarily restrained along any edges in contrast to the commonly imposed con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…However, when using this method, there is no guarantee that no natural frequency of the structure will be missed and the method may become computationally expensive and very difficult in achieving high accuracies, particularly in the high frequency range. Besides, the assembly procedure in this method seems to be quite tedious and cumbersome [28,29]. The superposition method on the other hand, pioneered by Lamé [38] and extensively used by Gorman in plate vibration problems (see his review paper [39]), has been shown to be an accurate and efficient method.…”
Section: Mathematical Basis Variation Based Differentiation Based (Stmentioning
confidence: 99%
See 2 more Smart Citations
“…However, when using this method, there is no guarantee that no natural frequency of the structure will be missed and the method may become computationally expensive and very difficult in achieving high accuracies, particularly in the high frequency range. Besides, the assembly procedure in this method seems to be quite tedious and cumbersome [28,29]. The superposition method on the other hand, pioneered by Lamé [38] and extensively used by Gorman in plate vibration problems (see his review paper [39]), has been shown to be an accurate and efficient method.…”
Section: Mathematical Basis Variation Based Differentiation Based (Stmentioning
confidence: 99%
“…However, different admissible functions should be chosen for different boundary conditions so that the formulation using the Rayleigh-Ritz method is not unique. Recently, a Fourier-series based analytical method (FSA) was proposed by Li and his co-authors [26][27][28][29] for plates with general boundary supports. In the FSA, a fictitious Fourier cosine series was used to satisfy first the elastic BC and then the GDE to form the final eigenvalue system expressed in terms of separate stiffness and mass matrices.…”
Section: Mathematical Basis Variation Based Differentiation Based (Stmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al [21] summarized the modified Fourier series method (MFSM) and proposed a complete set of analytical solutions for the transverse vibration of rectangular plates with general elastic boundary supports. Later on, the MFSM has been applied to solve many problems of plates with elastic boundary restraints, such as free vibration of two elastically coupled rectangular plates [22], modal analysis of general plate structures [23], and modeling analysis of elastically restrained panel [24]. This method is also used well in triangular plates [25], blades [26], circular plates [27], confocal annular elliptic plates [28], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these methods require the assumption of some geometry simplification. But recent formulations try to extend their use to more general structures, for example composed of rectangular plates [41,42,43].…”
Section: Introductionmentioning
confidence: 99%